Study of the Longitudinal Dynamics of Passenger Trains to Provide Recommendations for Their Control on New Sections of the Azerbaijan Railways - Ursulyak, L. V.; Bolotov, O. O. (Science and Transport Progress, 2025)
Purpose. In order to organize safe, longitudinal dynamics, train traffic on the sections of the Azerbaijan Railways that are being put into operation, the paper provides recommendations for controlling the movement of passenger trains and electric trains to realize the maximum possible speed, taking into account the technical capabilities of locomotives and the parameters of the longitudinal profile. Methodology. The estimation of the largest values of longitudinal accelerations was performed by means of computer modeling of longitudinal oscillations of passenger trains while they are moving at different speeds in areas with the most unfavorable parameters of the profile and track plan, which are superimposed on the train disturbances caused by the driver’s actions to control its movement. The paper presents mathematical modeling of the force characteristics of inter-car connections of passenger cars equipped with modernized rubber-metal absorbing devices. To confirm the validity of the mathematical model, the maximum values of longitudinal accelerations of cars and braking distances obtained as a result of mathematical modeling of passenger trains were compared with similar values obtained during experimental trips. Findings. Using computer modeling of longitudinal train oscillations, diagrams of the distribution of the largest longitudinal accelerations along the length of trains with different numbers of cars, the magnitude of braking distances, and braking times were obtained. For the proposed modes of train control, the dependence of the speed on the track coordinate is analyzed. It is noted that for the considered modes of operation of passenger trains and electric trains with the specified speeds on certain sections of railways, the level of longitudinal accelerations of cars does not exceed the values that will affect the safety of train traffic and the comfort of passenger travel. Originality. For the first time, the authors proposed a mathematical model of the power characteristic of the modernized absorber apparatus, which is used in passenger cars on the Azerbaijan Railways. The longitudinal load of electric trains and passenger trains, as well as speed curves in different modes of train operation on certain sections of the Azerbaijan Railways were investigated. Practical value. Based on the results obtained, recommendations for controlling the movement of passenger trains on real track sections to maintain a given speed, taking into account the technical capabilities of locomotives and longitudinal profile parameters, were provided.